Survey for Highly Pathogenic Avian Influenza from Poultry in Two Northeastern States, Nigeria - Ibrahim Waziri Musa; Paul Ayuba Abdu; Anthony Kojo Bedu Sackey; Sunday Blessing Oladele (Veterinary Medicine International)
Highly pathogenic avian influenza (HPAI) is a major global zoonosis. It has a complex ecological distribution with almost unpredictable epidemiological features thus placing it topmost in the World Organization for Animal Health list A poultry diseases. Structured questionnaire survey of poultry farmer’s knowledge, attitudes, and practices (KAP) in two Nigerian states revealed the presence of risk farming practices that may enable avian influenza high chance of introduction/reintroduction. There existed significant statistical association between farmer’s educational levels and AI awareness and zoonotic awareness (). Poultry rearing of multiage and species (81%), multiple sources of stock (62%), inadequate dead-bird disposal (71%), and access to live bird markets (LBMs) (62%) constituted major biosecurity threats in these poultry farming communities. Haemagglutination inhibition (HI) test detected antibodies against H5 avian influenza (AI) in 8 of the 400 sera samples; rapid antigen detection test kit (RADTK) was negative for all the 400 cloaca and trachea swabs. These results and other poultry diseases similar to AI observed in this study could invariably affect avian influenza early detection, reporting, and control. We recommend strong policy initiatives towards poultry farmers’ attitudinal change and increasing efforts on awareness of the implications of future HPAI outbreaks in Nigeria.